ANTECEDENTS OF JABODETABEK PATIENT’ INTENTION TO SEEK MEDICAL TREATMENT ABROAD - Ellen Viana; Rudy Pramono (SEAN Institute, 2023)
Approximately there are two thousand Indonesian people chose to travel abroad for health care treatment and causing 165 trillion rupiahs of state foreign exchange to flow abroad. The aim of this study is to seek the antecedent of Indonesian people in choosing treatment abroad using the theory of planned behaviour, electronic word of mouth (eWOM), and physical environment as the basis of the analysis and hypothesis development. This study was conducted quantitatively with a cross-sectional study design. The model used is a modification of previous studies and then tested on a population of people aged over 18 years and living in JABODETABEK. Sampling was done by purposive sampling method and obtained as many as 145 respondents. Partial least squares–structural equation modelling (PLS-SEM) is the analytical method used in this study, and the result shows that there is a positive influence between attitude, subjective norms, perceived behaviour control, eWOM, and physical environment on visit intention. Attitude and eWOM are the most important things in influencing someone to seek treatment abroad whereas a domestic hospital can increase public trust in healthcare in Indonesia by using online platforms to communicate.